A psychoanalytical attempt at the emergence and interpretation of narcissism in johann wolfgang von goethe's epistolary novel the sorrows of young werther - TEKİN, HABİB (My University, 2023)
Narcissism is an intriguing psychological phenomenon depicted in a variety of literary forms and manifestations. The 1774 publication The Sorrows of Young Werther by Johann Wolfgang von Goethe is an exceptional example. In this novel, the protagonist Werther is portrayed as a typical example of narcissistic traits that lead to his tragic end. Based on this state of mind, this paper will determine Freud\"s interpretation of narcissism in Goethe’s Werther. Some texts on melancholy, mourning, and narcissism will be consulted for this purpose. In his works, Freud describes various phases of narcissism formation, which are all illustrated and described in greater detail. This process was depicted in a diagram, and its stages were broken down. In his career, life, and work, the protagonist Werther will undergo the various phases of Freudian narcissism formation. Consequently, it will be investigated if the psychology that flourished decades later can also be applied to Werther and how the development of narcissism can be analysed letter by letter. Moreover, critical situations were identified and analysed in which narcissism and its origin, effect, and consequences can be depicted in an especially accurate manner. For these reasons, the psychoanalytic interpretation of the work is predominantly founded on Sigmund Freud\"s theory of melancholy and mourning and secondarily on the development of narcissism. In this regard, both texts Das Ich und das Es (1975) and Der Untergang des Odipuskomplexes (1989) by Sigmund Freud were selected for narcissism development as a theoretical framework.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Werther; Sorrow; Narcissism; Freud; Melancholy; Oedipus